Bangla grammar and spelling check using machine learning - Ahmed, Foysal; Khan, Md Shahriar; Arafin, MD Emon; Al Abir, Abdullah; Begum, Mumtahina (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.